2015
DOI: 10.1542/peds.2014-3290
|View full text |Cite
|
Sign up to set email alerts
|

Off-Label Use of Inhaled Nitric Oxide After Release of NIH Consensus Statement

Abstract: BACKGROUND: Inhaled nitric oxide (iNO) therapy is an off-label medication in infants ,34 weeks' gestational age. In 2011, the National Institutes of Health released a statement discouraging routine iNO use in premature infants. The objective of this study was to describe utilization patterns of iNO in American NICUs in the years surrounding the release of the National Institutes of Health statement. We hypothesized that iNO prescription rates in premature infants have remained unchanged since 2011.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 35 publications
2
57
0
1
Order By: Relevance
“…There are no data to support routine or rescue use of inhaled nitric oxide (iNO) in preterm babies [172]. Despite this, iNO continues to be used in many units, particularly for ill babies with severe respiratory failure and poor oxygenation [173,174]. There is an argument for rationalizing the use of iNO for specific populations of preterm infants, for example those with premature rupture of membranes or documented pulmonary hypertension and conducting further clinical trials [175,176].…”
Section: Managing Blood Pressure and Perfusionmentioning
confidence: 99%
“…There are no data to support routine or rescue use of inhaled nitric oxide (iNO) in preterm babies [172]. Despite this, iNO continues to be used in many units, particularly for ill babies with severe respiratory failure and poor oxygenation [173,174]. There is an argument for rationalizing the use of iNO for specific populations of preterm infants, for example those with premature rupture of membranes or documented pulmonary hypertension and conducting further clinical trials [175,176].…”
Section: Managing Blood Pressure and Perfusionmentioning
confidence: 99%
“…Recent reports showed that the rate of iNO utilisation in the treatment of pre-term neonates continues to increase in the USA [17] with no established evidence of the beneficial effects of iNO on survival in babies without bronchopulmonary dysplasia [3, 4, 18]. In this context, understanding the side-effects of iNO, including the rebound pulmonary hypertension upon iNO withdrawal, could be useful.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of off-label use of iNO in premature infants 23–29 weeks gestation utilizing the Pediatrix Medical Group Clinical Data Warehouse for the period 2009–2013 showed a relative increase of 23%, from 5.03% to 6.19% (p=.003). 78 iNO utilization rates were inversely proportional to gestational age; iNO was used in 13.9% of infants at 23–24 weeks compared to 0.6% of infants born at 33 weeks. The reason for use was not collected.…”
Section: Use Of Ino In the Preterm Infantmentioning
confidence: 96%
“…Several authors have speculated that the increase in oxygen saturation following iNO exposure leads neonatologists to attribute their survival to this physiologic response. 66,78 Finer and Evans suggest that evidence-based guidelines for the use of iNO in preterm infants should be developed by units. 66 Guidelines should leave room for individual judgment; however, they should also recognize the accumulated data which has shown the highest risk and lowest efficacy in premature infants <1000 grams.…”
Section: Use Of Ino In the Preterm Infantmentioning
confidence: 99%